American experience. - Nelson, Stanley, 1951-; Nelson, Stanley, 1951-; Nelson, Stanley, 1951-; Grant, Laurens (Academic Video Online, 2011)
Bernard Lafayette, Jr. was part of the Nashville, Tennessee, via Birmingham, Alabama, to Montgomery, Alabama ride, May 16-20, 1961.